Distinctive features of recognition for documents printed in the Romanian transitional alphabets - Tudor Bumbu; Lyudmila Burtseva; Svetlana Cojocaru; Alexandru Colesnicov; Ludmila Malahov (Computer Science Journal of Moldova, 2023)
In this paper, we summarize the research of digitization of documents printed by Romanian transitional alphabet. These printings are the most original Romanian historical documents, which makes our experience useful when researching OCR methods for similar alphabets.